The importance of organizational culture for humanitarian operations - Milošević Nikola (Viša ekonomska škola Peć, Leposavić, 2021)
The humanitarian setting poses a number of challenges to organizations, so it is important to respond in an adequate way. Organizational culture is a significant factor in organizational performance and can be a deciding factor between success and failure. Every organization has its own unique culture, whether management is aware of it or not. In order to perform in the most efficient way and to be able to carry the strategy into effect properly, humanitarian organizations need an adequate and strong organizational culture. Then, to strengthen the team's sense of purpose and help it move in a unified direction humanitarian principles and standards are developed. For the development of the organization timely establishment of value systems and patterns of behavior is very important. Organizational culture is important for internal structure as well as for external bonds among participants.